Effect of concentration on PVA solutions and its usage in recycling carbon fiber/polyamide 12 prepregs - Altinbay, Aylin (WALTER DE GRUYTER GMBH, 2024)
Polyvinyl alcohol (PVA) is a biodegradable synthetic polymer with high chemical resistance and excellent mechanical and oxygen barrier properties. Besides these superior properties, it is water-soluble, which provides its wide usage. However, its solubility depends on some factors. Although the temperature is one of these factors and increasing temperature could promote solubility, there is a solubility limit according to hydrolysis degree. In this study, PVA solutions at various concentrations were obtained by mixing fully hydrolyzed PVA1500 and water. Solutions were characterized by density, surface contact angle and dynamic viscosity measurements. Then, solvent casting was used to obtain films, and physical and mechanical properties were determined. Tensile test results showed optimum values at 10-12.5wt.% PVA concentration. Also, vacuum drying changed the mechanical behavior of films significantly at all concentrations. While ultimate tensile stress values almost doubled and modulus values increased approximately three times, elongations critically decreased. Solutions were also subjected to waste carbon fiber (CF)/polyamide 12 (PA12) prepregs for recycling purposes. Lay-up and compression molding processes were applied to produce CF/PA12 composites. It was seen that mechanical results were significantly increased with increasing PVA concentration.
Keywords: PVA; concentration; viscosity; joining; composite; recycling; CHARACTERISTIC RHEOLOGICAL FEATURES; POLY(VINYL ALCOHOL); POLYVINYL-ALCOHOL; BLENDING PROPERTIES; CRYSTALLIZATION; MISCIBILITY; BEHAVIOR; BARRIER; WATER; Materials Science